2003
DOI: 10.1128/jcm.41.7.2900-2907.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Magnitude of Intralaboratory Variability in a Sequence-Based Genotypic Assay for Human Immunodeficiency Virus Type 1 Drug Resistance

Abstract: We assessed the intralaboratory reproducibility of a system for sequencing human immunodeficiency virus type 1 (HIV-1) protease (PR) and reverse transcriptase (RT) by using replicate subanalyses of 46 plasma samples collected from HIV-1-infected, antiretroviral-experienced patients in order to determine the relative contributions of the different procedural steps to final sequence variability. Complete sequence concordance between duplicates of each sample was 99.4%. Complete and partial mismatches occurred sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
(29 reference statements)
1
25
0
1
Order By: Relevance
“…To address this we have performed replicate pyrosequencing experiments at two different steps of the protocol. We found that the RT and amplification steps contributed substantial error variation to frequency estimates, which is consistent with previous findings in the context of mixtures (Galli et al 2003). Additionally, replication of the sample extraction step revealed disproportionately greater reductions in reproducibility of frequency estimates, relative to contributions from RT-PCR and second-round PCR amplifications (supplementary text S1 and fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To address this we have performed replicate pyrosequencing experiments at two different steps of the protocol. We found that the RT and amplification steps contributed substantial error variation to frequency estimates, which is consistent with previous findings in the context of mixtures (Galli et al 2003). Additionally, replication of the sample extraction step revealed disproportionately greater reductions in reproducibility of frequency estimates, relative to contributions from RT-PCR and second-round PCR amplifications (supplementary text S1 and fig.…”
Section: Discussionsupporting
confidence: 79%
“…This must be considered alongside several other sources of error, some of which are not specific to NGS but compounded by NGS-specific error: (Peccoud and Jacob 1996). Variability in the observation of mixtures in HIV-1 pol bulk sequences has been attributed largely to this source (Galli et al 2003). Recombination at the RT-PCR step may also constitute a significant source of error.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance mutation reporting often varies between laboratories, even when identical samples are tested (9,17). While many interlaboratory discrepancies can result from differences in sample preparation (e.g., primer choice or stochastic variation), variation may be introduced by technicians as they subjectively review the assembled sequences (11).…”
mentioning
confidence: 99%
“…In previous work, we demonstrated that mixtures in population-based HIV-1 and hepatitis C virus sequences recapitulate the adaptation of the circulating virus population to immune variation in the host population owing to the similar time scales of transmission and selection in these viruses (59). The accurate interpretation of mixtures will ultimately require a comprehensive model that addresses the relative contributions of both population genetic (59) and experimental (28) processes. This model may be further complicated by the infrequent occurrence of coinfection or superinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing standards will require that we understand which aspects of the sequencing protocol contribute the most variability in detecting mixtures. For instance, Galli et al (28) previously noted that most discordances were due to the extraction and reverse transcription steps of processing patient samples.…”
Section: Discussionmentioning
confidence: 99%